Efficacy and safety of Shenqi Jiangtang Granules plus oral hypoglycemic agent in patients with type 2 diabetes mellitus: A systematic review and meta-analysis of 15 RCTs. Issue 5 (5th February 2021) - Li, Tianli; Li, Hongzheng; Wu, Yang; Wu, Qian; Zhao, Guozhen; Cai, Zhaolun; Pu, Fenglan; Li, Bo
Abstract: Objective: Shenqi Jiangtang Granules (SQJTG) has been widely used to treat patients with type 2 diabetes mellitus (T2DM). But whether there exists sufficient evidence on the efficacy of SQJTG in the treatment of T2DM is unclear. In order to assess the effects of SQJTG for T2DM, a systematic review and meta-analysis of randomized controlled trials (RCTs) were carried out. Methods: Eight databases, namely, PubMed, The Cochrane Library, EMBASE, Web of Science, Chinese National Knowledge Infrastructure, Chinese Scientific Journals Full-Text Database, CBM, and Wanfang database were searched up to May 2020. According to the Cochrane standards, the selection of study, the extraction of data, the assessment of study quality, and the analyses of data were carried out strictly. Then a fixed or random effects model was applied to analyze the outcomes. Results: Fifteen studies (N = 1392) in total conformed the inclusion criteria to this meta-analysis. Two subgroups were identified, based on different dose of SQJTG: oral hypoglycemic agent (OHA) vs OHA plus SQJTG (1 g); OHA vs. OHA plus SQJTG (1.5–3 g). The pooled results showed that, in comparison with OHA, OHA plus SQJTG significantly reduced fasting plasma glucose in both 1 g subgroup and 1.5–3 g subgroup; 2-hour post-meal blood glucose was also greatly reduced in the SQJTG 1 g subgroup and the SQJTG 1.5–3 g subgroup. Compared with OHA, SQJTG 1 g subgroup significantly reduced levels of glycated hemoglobin A1c, as well as the SQJTG 1.5–3 g subgroup. Homeostasis model-insulin resistance index was also reduced in both SQJTG 1 g subgroup and SQJTG 1.5–3 g subgroup; SQJTG group can also significantly reduce the total adverse events especially in reducing the incidence of hypoglycemia. Conclusions: SQJTG is an effective and safe complementary treatment for T2DM patients. This meta-analysis provides an evidence for the treatment in patients with T2DM. While owing to the high heterogeneity and the trials' small sample size, it's crucial to perform large-scale and strict designed studies.